The Gastroprotective Effects of the Ethanolic Extraction from Musa (ABB group) ‘Kluai Nam Wa’ Flower in Wistar Rats - Khamboonruang, Pattrawan; Anuntasethakul, Thiraporn; Navephap, Somphop; LeGrand, Supang Maneesri (KKU Science Journal, 2016)
The flower of Musa spp. has interested the scientific community due to its numerous pharmacological properties and potential therapeutic applications. The present study aimed to investigate the gastroprotective effects of the ethanolic extraction from Musa (ABB group) ‘Kluai Nam Wa’ flower (EF) on experimental models against gastric ulcer induced by absolute alcohol, indomethacin and swimming stress in Wistar rats. The EF was orally administered at dosages of 250, 500 and 1,000 mg/kg for 1 h prior to induction of gastric ulcer. The common parameters determined were ulcer index (UI), protection percentage (% protection), gastric secretion and gastric wall mucus content. The results demonstrated that pre-treatment with EF at doses of 250, 500 and 1,000 mg/kg showed a potent ulcerprotective effect in a dose-dependent manner which significantly (p<0.05) reduced ulcer index at the lowest dose (250 mg/kg) in all models as compared to the control group. Pre-treatment with EF at a dose of 1,000 mg/kg showed potential gastroprotection 78.80%, 70.26% and 68.73% in absolute alcohol, swimming stress, and indomethacin models respectively. The gastroprotective activity of EF involved an anti-secretory effect as it significantly (p<0.05) decreased gastric acidity and pepsin without any effect on gastric volume and total proteins when compared to the control group. Pre-treatment with EF promoted gastroprotective effect by significantly (p<0.05) increasing gastric wall mucus content and gastric pH when compared to the control group. The results suggest that EF presents anti-ulcer activities against absolute alcohol, indomethacin and swimming stress in Wistar rats. The gastroprotective activity of EF could involve promoting mucus secretion.